Defendiendo el futuro del arbitraje internacional - Born, Gary (Pontificia Universidad Católica del Perú, 2016)
The last 30 years have been a really exceptional time for international arbitration. The author resembles international arbitration with the SevenKingdoms of “Game of Thrones” where everything went right under the umbrella of the New York Convention.Gary Born states: “Winter is Coming” for international arbitration. The arbitration community should be prepared to defend itself from a metaphorical “armyof undead” who could demand more government control of the arbitration process in the future. In that regard, the author states that instead of beinghunted in defending arbitration, we ought to hunt a little bit. The time to stop fending off attacks and start going on the offensive against arbitration’s critics have come.

Los últimos 30 años han sido una época realmente excepcional para el arbitraje internacional. Gary Born lo asemeja a los Siete Reinos de “Juego de Tronos”, pues todo ha funcionado bien bajo el marco de la Convención de Nueva York. Sin embargo, según Gary Born: “se acerca el invierno” para el arbitraje internacional. La comunidad del arbitraje debe estar preparada para defenderse de un metafórico “ejército de muertos vivientes” que podría exigir un mayor control del gobierno sobre el arbitraje en el futuro. En ese sentido, el autor señala que en vez de ser cazados defendiendo el arbitraje, debemos cazar un poco. El momento de dejar de defenderse de los ataques y empezar a ir a la ofensiva contra los críticos del arbitraje ha llegado.
Addressing recent criticisms against international arbitrations
Keywords: Derecho; https://purl.org/pe-repo/ocde/ford#5.05.01